Influence of Investment, Wage Level, Inflation, Economic Growth and Community Economic Affairs Toward Welfare in The District City of Riau Island Province . - Tamami, Sastra; ., Ujianto; Ratih, Ida Aju Brahma (Archives of Business Research, 2018)
Provincial Government of Riau Islands continues to make efforts to improve the welfare of the community, especially in the wage sector, with various policies issued, either through the Minister of Manpower Regulation. Provincial authority as an Autonomous Region, changing the enactment of the Regional Minimum Wage into Provincial Minimum Wage. This research was conducted to solve the problem of community welfare in Regency of Kepulauan Riau Province Province. Under the title Influence of Investment, Wage Level, Inflation, Economic Growth and Community Economic Affairs Toward Welfare in The District City of Riau Island Province. His unit of analysis is the all of the city districts located in Kepualaun Riau Province. The data used in this study is a combination of secondary data in the form of coherent and cross-data called data polling. Concrete data covered the period 2010-2015, while cross-data covering all urban districts in Riau Islands Province. This research uses qualitative research methods, and data processing is done with Warp Partial Least Square (Warp PLS). The results showed that: 1). Investment has a significant effect on regional economic competitiveness. 2). Investment has a significant effect on economic growth. 3). Investment has a significant effect on people’s welfare. 4). Wage rate don’t has an insignificant effect on regional economic competitiveness. 5). Wage rates have a significant effect on regional economic growth. 6). Wage rates have a significant effect on people’s welfare. 7). Inflation has a significant effect on regional economic competitiveness. 8). Inflation don’t has a significant effect on economic growth. 9). Inflation has a significant effect on people’s welfare. 10). Economic growth has a significant effect on regional economic competitiveness. 11). Economic growth don’t has a significant effect on the welfare of local communities. 12). The competitiveness of regional economy has a significant effect on the people’s welfare.